Research on key concepts of economic technologies and their application in the development business - OKSENCHUK, Roman (Ways to Improve Construction Efficiency, 2025)
In the modern development business, economic technologies serve as a key factor in shaping an efficient, analytically grounded, and resilient management system. They combine digital tools, financial models, and analytical methodologies that transform the processes of planning, construction, and property operation into a single continuous value management cycle. The essence of economic technologies lies in the integration of managerial, informational, and investment functions within a digital environment that ensures transparency, accuracy, and adaptability of decision-making. Development companies use these technologies to create flexible project management models, enhance the efficiency of resource planning, forecast risks, and establish new formats of interaction with clients and partners. Digitalization of management enables a shift from intuition-based decisions to data-driven management, where the leading role is played by ERP, CRM, and BIM systems, KPI dashboards, and Business Intelligence tools. In the context of development activity, economic technologies create the foundation for sustainable growth, reduction of operational costs, and strengthening of enterprise competitiveness. They enable the management of not only financial flows but also brand value, reputational risks, and levels of social responsibility – factors that have become particularly significant under the influence of global ESG trends. A crucial role belongs to the integration of big data analytics and machine learning, which make it possible to forecast market trends, demand for real estate, and evaluate potential implementation scenarios for investment projects. This facilitates the transition to a new management paradigm – analytically-driven development, in which every decision results from multilayered digital analytics. Thus, economic technologies become not only a means of improving business efficiency but also the foundation for the strategic resilience of companies operating in a volatile economic environment. Their application defines an enterprise’s capacity for innovation, managerial flexibility, and integration into the global processes of the digital economy.